Karakteristik Petrologi dan Geokimia Batuan Gunungapi Berumur Oligosen Akhir - Miosen Di Daerah Gunung Muro, Kalimantan Tengah - Joko Wahyudiono (Jurnal Geologi dan Sumberdaya Mineral, 2017)
Mount Muro is located in Purukcahu District of Central Kalimantan and geologically dominated by Late Oligocene-Miocene volcanic rocks. The purpose of this research mainly to understand the geodynamic evolution, including rock type, magmatic suites and tectonic environment during Late Oligocen to Miocene of the research area. Eight samples from that region were collected and prepared for petrographic and geochemistry analyses. Petrography analysis using polarization microscope was   carried out for rock classification, whereas XRF and ICP were used mainly to detect the presence of major, trace and rare earth elements. Based on petrographic analyses the eight rock samples studied can be classified into basalt, andesite-basalt and diorite. Cross plot of weight percent SiO2  versus weight percent (Na2O + K2O) revealed that the rocks are differentiated into basalt, andesite-basalt, basalt trachy-andesite to andesite. The weight percent SiO2 versus weight cross plot percent K2O demonstrated that rocks samples of the studied area included in calc-alkaline magmatic series. This implies that the rock samples were originally from a convergent plate margin tectonic environment. The existence of Nb through in the spider diagram has been explained in terms of retention of this element in the source during partial melting. Keywords: petrology, geochemistry, tectonic, geodynamics, magmatic series